2020
DOI: 10.1089/scd.2019.0197
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulatory Potential of Exosomes Derived from Cancer Stem Cells

Abstract: Head and neck squamous cell carcinomas (HNSCCs) are malignancies that originate in the mucosal lining of the upper aerodigestive tract. Despite advances in therapeutic interventions, survival rates among HNSCC patients have remained static for years. Cancer stem cells (CSCs) are tumor-initiating cells that are highly resistant to treatment, and are hypothesized to contribute to a significant fraction of tumor recurrences. Consequently, further investigations of how CSCs mediate recurrence may provide insights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 151 publications
(140 reference statements)
0
11
0
Order By: Relevance
“…CSCs, a small population of cancerous cells, are tumor-initiating cells and include a group of quiescent self-renewing cell types which pre‐exist in primary malignant tumors and localized within the tumor niches bearing enriched functional potential to drive tumor growth, to reconstruct their heterogeneity and to make changes in tumor regenerative capacity [ 134 , 135 ]. The different cell surface markers are often applied to identify and enrich CSCs, including CD44, CD24, and CD133 [ 136 ].…”
Section: Role Of Resveratrol In Glioblastoma Treatmentmentioning
confidence: 99%
“…CSCs, a small population of cancerous cells, are tumor-initiating cells and include a group of quiescent self-renewing cell types which pre‐exist in primary malignant tumors and localized within the tumor niches bearing enriched functional potential to drive tumor growth, to reconstruct their heterogeneity and to make changes in tumor regenerative capacity [ 134 , 135 ]. The different cell surface markers are often applied to identify and enrich CSCs, including CD44, CD24, and CD133 [ 136 ].…”
Section: Role Of Resveratrol In Glioblastoma Treatmentmentioning
confidence: 99%
“…The ability to dephosphorylate ATP to form ADO was documented in exosomes from bladder (HT1376 line), colon cancer (CaCo line) and in malignant effusions of mesothelioma patients. ADO promoted a negative regulation of T cells in the TME [170]. It was shown that exosomes from the prostate carcinoma cell line DU145, expressing CD39 and CD73, inhibited DC activities that resulted in an immunosuppressive environment [171].…”
Section: Cell Type Observations Referencesmentioning
confidence: 99%
“…In Th17 cells, differentiated in vitro by a combination of IL-6 and TGF-®, IL-6 through Stat3 positively regulated NT5E expression, while TGF-β through Gfi-1 repressed its expression, but the cells displayed an immunosuppressive phenotype [178]. Moreover, the processing of RNAs coding for NT5E is regulated by a miRNA group, the presence of this miRNA contributes to the role of CD73 in cancer [170].…”
Section: Cell Type Observations Referencesmentioning
confidence: 99%
“…Many properties associated with cancer-derived exosomes (CDEXs) overlap with the newly discovered functions of CSCEXs. However, it is important to note that many studies have reported difficulties in distinguishing exosomes released from CSCs from similar subclones within complex tumor tissues [ 70 ]. Currently, only a few studies have reported the physiological functions of CSCEXs, which are summarized in relation to the known markers and cargo in the above sections ( Table 1 ).…”
Section: Biological and Physiological Roles Of Cscexsmentioning
confidence: 99%